The Study Of The Soliton Solutions In (2+1) Yang-Mills-Higgs Field Theory - Koh , Pin Wai (2012)

(untitled)
The purpose of this thesis is to study the solitonic solutions in (2+1) dimensions of the Yang-Mills-Higgs eld theories. Soliton is dened as solitary, traveling wave pulse solution of nonlinear ordinary dierential equations (ODEs) or partial dierential equations (PDEs). In order to nd the soliton, we must solve the dierential equations either analytically or numerically.